Activities of civil society institutions in the context of the concept of political participation: New challenges and additional features - Dreval, Vitaly (Działania instytucji społeczeństwa obywatelskiego w kontekście koncepcji partycypacji politycznej: Nowe wyzwania i dodatkowe cechy, 2022)
This paper is devoted to the peculiarities of the relationship between civil society institutions and public authorities under the current complicated circumstances. It is noted that civil society is characterised by clear functional or ‘activity’ distinguishing features, representing the dynamic system of interaction between people in the process of aggregation and upholding of certain important issues. It is in this sense that the problem of participation and, in a more specific sense, political participation becomes especially relevant. Such participation is the substantive basis of the concept of participatory democracy, which refers to the ability of citizens not only to participate in elections, referendums and plebiscites, but also directly in the political process – in the preparation, adoption and implementation of government decisions. Today, the complex problematics of civil society institutions in the context of the concept of political participation is gaining additional relevance. This is primarily due to two important factors: firstly, the in-depth understanding of the essence of representative democracy with the emphasis on the involvement of citizens in participation in the government; secondly, the significant opportunities of the use of Internet resources. Moreover, in this case, the principle is that participatory democracy does not replace, but complements representative democracy in its classical sense (mechanisms and principles of these two forms do not coincide, so they may not replace but complement each other). In our opinion, purely practical importance in the implementation of the concept of participatory democracy should be given to managerial, administrative and actually participatory models. Moreover, in practice, these models cannot be implemented in their pure forms and are embodied in a kind of hybrid form with a combination, depending on the current situation and different components of the outlined models. In this case, we should talk about updating the entire system of power, abandoning some traditional forms of work and mastering new mechanisms in the implementation of the idea that “the state is the civil society”!
Zeszyty Naukowe Collegium Witelona, nr 45(4)/2022, s. 73-84
Keywords: democracy; participatory democracy; public sphere; institutions; civil society institutions; demokracja; demokracja uczestnicząca; sfera publiczna; instytucje; instytucje społeczeństwa obywatelskiego